Pengaruh Edukasi Audiovisual Berbasis Syariah terhadap Pengetahuan, Perilaku, dan Sikap Pencegahan Kanker Serviks dengan Deteksi Dini di Puskesmas Tlogosari Kulon Semarang - Annisa Miftahul Jannah; Tutik Rahayu; Sri Wahyuni (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Background: Early detection of cervical cancer includes an IVA examination or Pap smear. This test is used to identify cervical cancer and in Islam it is also recommended to maintain (hifdz an-nafsa), namely maintaining reproductive health related to offspring (hifdz an-nasl). The aim of this research is to determine the effect of sharia-based audiovisual education on knowledge, behavior and attitudes towards preventing cervical cancer. Purpose: to determine the effect of sharia-based audiovisual education on knowledge, behavior and attitudes towards preventing cervical cancer. Method: This type of research uses quantitative with a quasi-experimental research design in the form of one-group without control and this research uses an accidental sampling technique with 41 respondents. Data was taken before and after the intervention was given and then analyzed statistically using the Wilcoxon test. Results: The results of the Wilcoxon test research showed that z knowledge calculation was -5.667, behavior -4.583, and attitude calculation -5.831 with an asym.sig value of 0.000. This shows that the p value <0.05 was a difference after the pre-test and post-test of providing audiovisual education. Conclision : There is an influence of providing audiovisual education on knowledge, behavior, attitudes, prevention of cervical cancer with early detection in the working area of ​​the Tlogosari Kulon Health Center, Semarang.